Applying Islamic Practices in Increasing Muslim’s Participation in Community HealthPromotion at Tha Sala Community Hospital, Changwat Nakhon Si Thammarat - Ratanasombat, Kitti (Journal of Health Science of Thailand, 2017)
This participatory action research study was aimed at raising community participation in health promotion among Muslims applying Islamic practices. Target groups included newborns, adolescents, adults and elderly. Participants in the study were religious leaders, community leaders, members of local administrative offices, members of civil health organizations as well as staffers of Tha Sala hospital. Results revealed that health activities could be integrated into Islamic way of life. This in turn created active participation in health promotion among Muslim communities. The activities included Azan for newborns (as welcoming pray). Circumcision for boys, preparation training for soon-to-be pilgrims, exercises and promotion for healthy eating behavior. These activities led to healthcare at individual, family and community levels. This participation, based on community own awareness (bottom up), resulted in health promotion activities which were appropriate to the religion of the community. It built up feelings of ownership and participation at all steps of health promotion. Quantitatively, results showed that 87.91 percent of the participants were highly satisfied and 12.09 percent were moderately satisfied with health promotion activities.